The Impact of School Management Misconceptions on Student Encouragement of Student Acceptance in Primary Schools - Soedjono Soedjono (International Journal of Research in Education, 2023)
The phenomenon of schools closing or being merged seems to be accepted by the public, but internally it is one of the failures of school management in maintaining the continuity of education. This research aims to explore school strategies to restore public trust through improving the quality of education. The methods used are the critical method, dialectical method, and scholastic method. This research is included in library research. The author tries to find data, and theories related to the issues raised in various literature or references that the author finds and then compares them using the method mentioned above. The research results show that management misconceptions are caused by various deficiencies ranging from lack of understanding to low managerial competence of school principals, which has an impact on the low quality of output, resulting in low public enthusiasm for the school. The efforts made by the school are expected to be comprehensive, both internal and external, including, 1) strengthening the learning community in the school. This community can be used as an effort to strengthen the competency of all human resources in the school, starting from the principal, teachers, and education staff. ; 2) creating a comfortable school ecosystem, comfortable not only for students but also for teachers and educational staff at the school; 3) collaboration with people and society, an effort that is no less important than the others, because this effort is like a double-edged sword, the context is to work together to improve the process and understanding of the quality measures of educational outcomes.